Effects of Nutrient Deficiencies on the Root Regenerating Potential and Growth of Pinus caribaea and Pinus kesiya Seedlings - Abod, Sheikh Ali (1990)
Successful plantation establishment requires the production of seedlings with high root regenerating potential (RRP) to beplanted in an enviroment which facilitates the production of new roots. Numerous factors in the nursery and in thefield influence RRP. This study examines the effects of a deficiency of two important essential elements, nitrogen and orphosphorus commonly deficient in tropical soils, on the RRP and growth of Pinus caribaea and Pinus kesiya seedlings. Given an adequate supply ofnutrients before transplanting in nutrient deficient sites, P. caribaea and P. kesiya showed a high capacity to regenerate root following root pruning and replanting into conditions oflimited nutrient supply (-N, -P& -NP). Seedlings grown inF (full nutrients) and -P conditions were taller and had thicker stem diameter than in -N or -NP. The results also show that P. kesiya had a higher RRP than P. caribaea despite the shorter mean height of the former species at the start ofthe experiment. The practical implication of the results to nursery cultural practices and tree establishment is discussed.